2001
DOI: 10.1152/ajpregu.2001.280.6.r1799
|View full text |Cite
|
Sign up to set email alerts
|

Social stress induces glucocorticoid resistance in macrophages

Abstract: Stress-induced levels of plasma glucocorticoid hormones are known to modulate leukocyte function. These experiments examined the effects of a social stressor on the responsiveness of peripheral immune cells. Male mice experienced six evening cycles of social disruption (SDR), in which an aggressive male intruder was placed into their home cage for 2 h. Although circulating corticosterone was elevated in SDR mice, they had enlarged spleens and increased numbers of splenic leukocytes. Splenocytes from SDR and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
221
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(255 citation statements)
references
References 29 publications
32
221
1
1
Order By: Relevance
“…These findings converge with evidence from studies of rodents, which experimentally manipulate exposure to stressors, and find that it diminishes sensitivity to glucocorticoidmediated signaling, both in the immune and nervous systems (19,44). They also converge with a recent microarray profile of socially isolated individuals, which documented a similar pattern of diminished GR-and heightened NF-κB-dependent transcription (29).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These findings converge with evidence from studies of rodents, which experimentally manipulate exposure to stressors, and find that it diminishes sensitivity to glucocorticoidmediated signaling, both in the immune and nervous systems (19,44). They also converge with a recent microarray profile of socially isolated individuals, which documented a similar pattern of diminished GR-and heightened NF-κB-dependent transcription (29).…”
Section: Discussionsupporting
confidence: 80%
“…Although the design precludes inferences about the direction of causal relationships, it is difficult to conceive of plausible reverse-directionality explanations for the findings. Moreover, covariance analyses ruled out a variety of potential demographic, behavioral, and biomedical confounders, and the results converge with experimental studies in animals, wherein the causal influence of stressors on sensitivity to glucocorticoid signaling has been established (19,44). Nonetheless, the findings need to be considered preliminary until they have been substantiated with larger samples, more rigorous prospective designs, additional functional indicators of glucocorticoid sensitivity, and assessments of other hormonal response systems (e.g., the sympathetic nervous system).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies have demonstrated that repeated social stress in mice is associated with decreased GC sensitivity of immune cells and excessive inflammation Engler et al, 2005;Johnson et al, 2004;Merlot et al, 2004;Sonoda et al, 2005;Stark et al, 2001). For example, lipopolysaccharide (LPS)-stimulated splenocytes from mice that repeatedly experienced acute encounters with an aggressive conspecific exhibited considerably higher cell survival in the presence of corticosterone (CORT) and showed greatly enhanced production of pro-inflammatory cytokines compared to splenocyte cultures from non-stressed controls (Avitsur et al, 2005Merlot et al, 2004;Stark et al, 2001). The decrease in splenic GC responsiveness was only observed after stimulation with LPS whereas unstimulated cells did not differ in their ex vivo response to CORT.…”
Section: Introductionmentioning
confidence: 99%